THE STRUCTURE AND COMPONENTS OF DEVELOPING VOLITIONAL QUALITIES IN PRIMARY SCHOOL STUDENTS (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The need to study the problem of motives in children aged 7-10, an important component of the personal development of a primary school student, is substantiated by the method of comparative-logical analysis. The article provides scientific information on the need to provide optimal conditions for the development of a young person, the manifestation of his abilities and the realization of his potential as a bright personality, the harmonious combination of personal interest in a particular type of activity and a free, creative attitude to life.